(untitled) - Rosenauer, Johnnie L (Mason, OH, 2007)
Rosenauer’s Effective Real Estate Sales and Marketing provides the reader with an overview of the relationship between marketing and sales and has a logical sequence of preparation steps for successful selling. These proven techniques can serve as an effective tool for beginners in the field and as a reminder for the sales veterans looking to review approaches that work. The author explains the marketing of real estate, the uniqueness of the sales process, and some of the advantages and disadvantages to being a real estate salesperson. Rosenauer offers information on understanding consumer behavior, effective communication, marketplace specialization, self-motivation, time management, record-keeping, prospecting, qualifying, and presenting and negotiation offers
Keywords: Real estate business,Real estate agents